Combination of photoperiod and temperature manipulation, and LHRHa treatment permits prolonged spawning of Atlantic salmon, Salmo salar - King, Harry; Pankhurst, Ned (Société Française d'Ichtyologie, 2008)
Female Atlantic salmon (Salmo salar) were exposed to a natural, or an advanced photoperiod from the austral summer solstice under natural or advanced temperature conditions, and injected with a commercial LHRHa preparation or vehicle. This created six photothermal- and LHRHa-treatment combinations, which generated a more than 4-fold increase in the total duration of the spawning period.